Implementasi Penerapan Prinsip Corporate Social Responsibility (CSR) Bidang Lingkungan pada CV Batik Murni - Nela Nafaza Kumala; Diah Hari Suryaningrum (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2025)
Corporate Social Responsibility (CSR) is one of the important points that need to be done by every business actor in carrying out their business activities. However, in its implementation, there are still many business actors who do not care about their social responsibility, especially in the environmental field. The absence of the application of Corporate Social Responsibility (CSR) principles in the environmental field can pollute the area around industrial sites. In addition, poor CSR implementation can also endanger the health of the surrounding community. Therefore, the author conducted research on the implementation of CSR principles in the environmental field in CV Batik Murni. The purpose of writing this research is to find out how CSR is implemented in CV Batik Murni, whether it has been implemented properly or not. In this study, the author uses a qualitative research method with a descriptive analysis approach. In this research, the author uses primary data and the data collection method is carried out by interviews, observations, and documentation. The result of this research is that CV Batik Murni has implemented the principles of Corporate Social Responsibility (CSR) in the environmental sector well. This is evidenced by the availability of Wastewater Treatment Plants (IPAL) and recycling fabric waste in the form of defective fabrics and patchwork.